Contribution of Planning And Media Toward Management of Learning Quality that is Implemented Teacher Junior High School Sub District Koto Tangah Padang - Soimah, Soimah; Marsidin, Sufyarma; Jamna, Jamaris (International Journal for Educational and Vocational Studies, 2020)
The background of the problem in this study is that there are still some teachers who teach without making a good teaching plan, are less skilled in using teaching media, are less able to activate students and less able to make assessment analyzes. The purpose of this study 1) the contribution of planning to the management of the quality of learning of state junior high school teachers Koto Tangah Padang, 2) Learning Media's contribution to the management of the quality of learning carried out by state junior high school teachers Koto Tangah Padang, 3) contribution of Planning and instructional media to the management of the quality of learning undertaken by state junior high school teachers Koto Tangah Padang.  This type of research uses a quantitative correlational method. The population in this study were 310 junior high school civil servant teachers in Koto Tangah District. The sample uses stratified proportional random sampling technique, so that the sample in this study amounted to 67 people. Data collection techniques using questionnaires. Data analysis techniques in this research are data description, test requirements and hypothesis testing. The results of this study 1) Learning planning contributes to the management of the quality of learning carried out by teachers of the State Junior High School in Koto Tangah District of Padang with a contribution amount of 23.3% by 24.4%, 3) Planning and media together contribute to the management of learning quality by 36.5%. This explains that to improve the management of good and ideal quality of learning should be done through improved learning planning and learning media.